World Bank Research Digest, Vol. 5(4) - World Bank (Washington, DC, 2014)
In this issue: generating jobs in developing countries: small versus young firms; measuring trade in a world of fragmented production; radio access and service delivery in Benin; trends in adult mortality around the developing world; eight questions about brain drain; who uses bottled gas in developing countries?; how much does infrastructure contribute to Gross Domestic Product (GDP) growth?